The Influence of Leadership Style, Motivation, and Work Discipline on Employee Performance at the Agency for Personnel and Human Resource Development of South Tangerang City - Putri Yulianti; Diana Hasan (Dinasti Publisher, 2025)
This study aims to analyze the influence of leadership style, work motivation, and organizational culture on employee performance at the South Tangerang City Personnel and Human Resources Development Agency (BKPSDM). The research method used is quantitative method with data collection techniques through questionnaires distributed to employees at BKPSDM. The data obtained were analyzed using multiple regression analysis to see the effect of each independent variable on the dependent variable. The results showed that leadership style, work motivation, and organizational culture simultaneously and partially had a significant effect on employee performance. The organizational culture factor has a dominant influence compared to the other two factors. These findings provide important implications for human resource management, especially in efforts to improve employee performance through strengthening effective leadership styles, providing optimal work motivation, and developing a supportive organizational culture.